EQUAL RIGHT OF CITIZENS TO ENROLL IN THE PUBLIC CIVIL SERVICE OF THE REPUBLIC OF UZBEKISTAN - Avezova Eleonora Paraxatovna (Scholars Digest Publishing, 2023)
This article is devoted to the analysis of the equal right of citizens to engage in public civil service. She explores the principles related to hiring and employment in the State apparatus, and focuses on the need to ensure equal opportunities for all citizens, regardless of their gender, race, ethnicity, religion or other factors that may lead to discrimination. The article provides an overview of international regulations governing equality in the civil service, including international conventions and treaties. The article analyzes national legal acts aimed at achieving equality in access to public service and overcoming discriminatory obstacles.
Keywords: public civil service, equality, discrimination, justice, meritocracy, professionalism.